Bee Sting Rhabdomyolysis: A Clinical Case Study Investigating Elevated Procalcitonin Levels Amidst Biochemical Muscle Injury - Anwar, Zara; Khakwani, Muhammad Khan; Tahir, Anoosha (Universitas Brawijaya, 2025)
Bee stings, although a nuisance, seem easy to deal with, causing only mild symptoms in the majority of people, but severe systemic reactions, like anaphylaxis or rhabdomyolysis, can rarely happen. Here is an unusual case report of a 75-year-old man with over a hundred bee stings, which resulted in elevated creatinine phosphokinase (CPK) levels, acute kidney injury (AKI), and increased markers of inflammation like C-reactive protein (CRP), white cell count and procalcitonin levels (PCT). Here, we highlight particular attention to procalcitonin, a marker sensitively used to differentiate between bacterial infections and other causes of inflammation. It was significantly elevated to 350 times above its normal upper range despite the patient not exhibiting any signs or symptoms of the disease. The patient made a complete recovery with supportive care, and all his biochemical markers of muscle injury and inflammation and AKI improved to baseline. Here, the authors highlight that clinicians should be aware that PCT can be spuriously elevated in rhabdomyolysis and does not automatically equate to a bacterial infection, re-iterating the need for reasonable antimicrobial use in this situation.